2010
DOI: 10.1097/bpo.0b013e3181efb888
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Posterior Sloping Angle in Predicting Contralateral Slipped Capital Femoral Epiphysis

Abstract: Level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 22 publications
2
30
0
Order By: Relevance
“…Nonetheless, these were the only angles that presented statistically significant correlation, in our study, showing that physeal sloping in the lateral view appears to be an important factor for the prediction of the occurrence of physeal epiphysiolysis of the proximal femoral region. This finding is consistent with the study conducted by Park et al., 25 who demonstrated the usefulness of the posterior sloping angle in the prediction of bilateral involvement.…”
Section: Discussionsupporting
confidence: 93%
“…Nonetheless, these were the only angles that presented statistically significant correlation, in our study, showing that physeal sloping in the lateral view appears to be an important factor for the prediction of the occurrence of physeal epiphysiolysis of the proximal femoral region. This finding is consistent with the study conducted by Park et al., 25 who demonstrated the usefulness of the posterior sloping angle in the prediction of bilateral involvement.…”
Section: Discussionsupporting
confidence: 93%
“…They calculated the number needed to treat to prevent one slip as 1.9 in their group. Park et al 7 evaluated the efficacy of the posterior sloping angle in predicting contralateral slip in a case control study of 102 patients. They concluded that for a posterior sloping angle cutoff of 12.66°, they would have a number needed to treat of 3.4.…”
Section: Discussionmentioning
confidence: 99%
“…Zenios et al 6 demonstrated good interobserver and intraobserver reliability of this measurement, and Park et al 7 demonstrated its use for predicting contralateral slip in a relatively large series. However, currently, to our knowledge, the posterior sloping angle is not widely used in the treatment of slipped capital femoral epiphysis.…”
mentioning
confidence: 91%
“…Barrios et al reported that the contralateral PSA was an important predictor for a subsequent slip [16]. Park et al and Phillips et al performed a further assessment of PSA [18,19]. The former reported that the cutoff value for prophylactic pinning was a PSA of 13°in girls and the latter reported that it was a PSA of 14°.…”
Section: Discussionmentioning
confidence: 99%
“…Some risk factors have been reported such as a younger age at the initial SCFE presentation [7,8], endocrine disorders [14], and renal failure [15]. A larger posterior sloping angle (PSA) in the contralateral hip has also been reported to be a significant risk factor for subsequent slip, and cutoff values for prophylactic pinning ranging from 12°to 14.5°have been identified [16][17][18][19]. These studies focused on the difference between the symptomatic and asymptomatic hips; however, little is known regarding subclinical posterior inclination of the capital femoral epiphysis in the contralateral hip in unilateral SCFE patients to our knowledge.…”
Section: Introductionmentioning
confidence: 99%